Effectiveness of Hybrid Solar Power Plant Integration in Wastewater Treatment: A Sustainable Approach to Water Crisis - Akrim, Djusdil; Buraerah, Muhammad Fikruddin; Swandi, Ahmad; Rahim, Abdurrachman; Yusuf, Andi Rumpang; Firmiaty, Sri; Rande, Hasniar Ambo; Syaiful, Andi Zulfikar (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2025)
This study evaluated the effectiveness of a solar-powered Wastewater Treatment Plant (WWTP) integrated with a water filtration system in improving water quality. This study employed an experimental approach, comparing influent and effluent water quality to determine treatment efficiency. The results showed significant improvements in water parameters, with pollutant removal efficiencies of 31.54% for Total Dissolved Solids (TDS) and 15.22% for pH reduction. The Dissolved Oxygen (DO) increased by 29.41% due to enhanced aeration. However, Electrical Conductivity (EC) increased by 46.07%, indicating the presence of dissolved ions post-treatment. The anaerobic-aerobic process effectively degrades organic pollutants, supported by bacterial activity, while the filtration system enhances water clarity and odor reduction. Despite these positive outcomes, the study has limitations, particularly the lack of Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) measurements, which restricts a comprehensive assessment of organic pollution removal. Future research should incorporate these parameters to provide a more holistic evaluation of wastewater treatment performance.